Sharing Images, Rethinking Rock Art heritage: A Photovoice Project with the !Xun and Khwe Communities of Platfontein (South Africa) - (:unkn) unknown (My University, 2024)
This article reflects on a photovoice project carried out in 2022 with San communities in South Africa. The project is the result of a participatory and collaborative approach involving an interdisciplinary team of researchers (ANR COSMO-ART), South African academic and cultural institutions, and two local NGOs. The study took place in Platfontein (Northern Cape, South Africa), among the !Xun and Khwe war refugees from Angola and Namibia, who, in 1997, became custodians of a South African rock art site. Charged with studying the relationship between these communities and their rock art heritage, we discuss in this article how photovoice contributes to the emergence of an understanding of heritage “from below”, which differs significantly from a nationalist, touristic, and economic perspective, and instead highlights a vision of heritage rooted in people’s everyday practices and experiences.
Keywords: African Research